Role of EBUS-TBNA in Mediastinal Staging of NSCLC Patients - Kunal B. Gala; Nitin S. Shetty; Saketh Rao; C.S. Pramesh; Sabita Jiwnani; Virendra Kumar; Sandeep Tandon; Maheema Bhasker; Rajiv Khushal; Suyash Kulkarni (Journal of Clinical Interventional Radiology ISVIR)
Purpose Mediastinal staging in non-small-cell lung carcinoma (NSCLC) is essential for appropriate treatment. Invasive mediastinal staging is necessary and mediastinoscopy has been the gold standard, but it is associated with morbidity. The aim of this study is to evaluate the efficacy of endobronchial ultrasonography transbronchial needle aspiration (EBUS-TBNA), compare it with mediastinoscopy, and assess the endosonographic features of lymph nodes for prediction of metastasis.